Synthesis of Tubulin Inhibitors with Variable Molecular Hinges for the Attachment of Aminopeptidase N Targeting Moieties - ANWAR, ZEESHAN (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2019)
This thesis includes synthesis of various tubulin binding agents and their incorporation in to novel dual acting hybrids, which along with the tubulin inhibition also exhibit aminopeptidase N (APN) inhibition activities. This thesis begins with an overview of the process of angiogenesis, the tumour vasculature network and the differences between tumor and normal vascular systems. The two main therapeutic approaches, by targeting angiogenesis and the newly formed vascular network, are also discussed. Moreover the concept of targeted therapy utilising the multifunctional enzymatic receptor APN is also presented along with various different hybrid drug approaches. The first chapter closes with a brief overview of the principal aims of the project. The initial focus of chapter 2 was the synthesis of 4-arylcoumarin derivatives having tetramethoxy arrangement. The work described in this chapter then progressed towards thionation of the carbonyl moiety at position 2 as this group can be replaced with a series of incoming nucleophiles unlike its carbonyl counterpart. Having successfully completed this transformation a series of suitable linker units were attached to this position primarily centred around oxime and hydrazone derivatives. Introduction of alcohol, aldehyde, carboxylic acid and amine functionalities at position 3 of the 4-arylcoumarins then follows. Significant emphasis in the later part of the chapter involves the double functionalisation of the 4-arylcoumarin with a phenolic group on the A-ring and an aniline group on the C-ring, as the chapter closes with an evaluation of the newly synthesised compounds as inhibitors of tubulin polymerisation. The synthesis of the phenstatin series in chapter 3 focuses on introducing additional hinges onto their structure principally based around a catechol structure on the A-ring while the B-ring was represented by a substituted aniline or phenol ring. This chapter also discusses the synthesis of phenstatin-like compounds, having a propanal side chain, an ideal functional group for both derivatisation and for conjugation of APN targeting moieties. These compounds were then evaluated as inhibitors of tubulin polymerisation. Chapter 4 centres on exploring the concept of hybrid drug therapy and employing it for the delivery of different tubulin binding agents whose synthesis is described in chapters 2 and 3. This chapter involves the incorporation of APN targeting moieties onto the tubulin binding agents for the purpose of creating hybrid drugs that have the capacity to inhibit both APN and tubulin polymerisation. Chapter 5 presents the experimental procedures used in the synthesis, characterisation of compounds as well as the procedures utilised for APN inhibition and tubulin polymerisation assay.
APPROVED